2018
DOI: 10.1002/adfm.201803822
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Models for Neurogenesis and Repair in 3D

Abstract: Development and maturation of vascular and neuronal tissues occurs simultaneously in utero, and are regulated by significant crosstalk. Here, the development of a 3D tissue system to model neurogenesis and recapitulate developmental signaling conditions is reported. Human umbilical vein endothelial cells (HUVECs) are seeded inside channels within collagen gels to represent nascent vascular networks. Axons extending from chicken dorsal root ganglia grow significantly longer and preferentially toward the HUVEC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…This could result in broad research implications in fundamental research, drug discovery, and personalized healthcare. Particularly, 3D in vitro platforms have been used to replicate the physiological cell‐cell and cell‐ECM interactions that could accelerate the development of new therapies …”
Section: Nervous System On a Chipmentioning
confidence: 99%
See 1 more Smart Citation
“…This could result in broad research implications in fundamental research, drug discovery, and personalized healthcare. Particularly, 3D in vitro platforms have been used to replicate the physiological cell‐cell and cell‐ECM interactions that could accelerate the development of new therapies …”
Section: Nervous System On a Chipmentioning
confidence: 99%
“…Another application of 3D printing would be to engineer vascular networks and neural networks to form a neurovascular system. Recently, Grasman et al reported the development of a 3D in vitro vascularized neural tissue model for neurogenesis and neural repair . The model contained an endothelialized microchannel lined by human umbilical vein endothelial cells (HUVECs), acting as a vascular conduit within a 3D collagen hydrogel which served the role of the ECM matrix.…”
Section: Nervous System On a Chipmentioning
confidence: 99%
“…From an ethical point of view, in vitro studies using cutting-edge techniques are clearly warranted to reduce the number of animals devoted to early stage in vivo experiments (Geuna et al 2016), and recent progress on the sector of lab-on-a-chip devices will further broaden the possibilities for this (Mobini et al 2019). Refined and sophisticated in vitro models are already available today, e.g., those evaluating neurite outgrowth (1) from dorsal root ganglia into a three-dimensional matrix (Bozkurt et al 2009;Grasman et al 2018) or (2) even from spinal cord slices into peripheral nerve segments or nerve guide materials (Vyas et al 2010;Siddique et al 2014). These models, however, are yet difficult to establish and to propagate.…”
Section: Translational Aspects Should Already Be Considered For In VImentioning
confidence: 99%
“… Illustration of the implementation of recently developed bioreactors in the production of an MC‐based 3D construct (a) Meso‐OFR (image adapted from [103]), (b) Perfusion bioreactor (image adapted from [104, 105])…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Post‐processing of the 3D structure can also be achieved using a perfusion bioreactor. These reactors improve mass transfer not only on the external surfaces of tissue scaffolds, but also around internal areas, stimulating tissue growth and maturation in a homogeneous manner [116, 117] In the work of Zhang et al [118] and Grasman et al [104] a perfection reactor was used for the integration of vascular cells into silk scaffolds (Fig. 4 b ).…”
Section: Future Perspectivesmentioning
confidence: 99%